Tested communication strategies for providing information to patients in medical consultations: A scoping review and quality assessment of the literature. Issue 8 (August 2021) - Menichetti, Julia; Lie, Hanne C.; Mellblom, Anneli V.; Brembo, Espen Andreas; Eide, Hilde; Gulbrandsen, Pål; Heyn, Lena; Saltveit, Kristina H.; Strømme, Hilde; Sundling, Vibeke; Turk, Eva; Juvet, Lene K.
Highlights: Tested strategies for providing medical information are heterogeneous. The methodological quality of information provision studies is moderate. We found four categories of differently used information giving strategies. Cognitive aid strategies were the most frequently tested strategy. Information giving strategies were rarely theoretically derived. Abstract: Objectives: To systematize the scientific knowledge of empirically tested strategies for verbally providing medical information in patient-physician consultations. Methods: A scoping review searching for terms related to physician, information, oral communication, and controlled study. Four pairs of reviewers screened articles. For each selected study, we assessed the quality and summarized aspects on participants, study, intervention, and outcomes. Information provision strategies were inductively classified by types and main categories. Results: After screening 9422 articles, 39 were included. The methodological quality was moderate. We identified four differently used categories of strategies for providing information: cognitive aid (n = 13), persuasive (n = 8), relationship- (n = 3), and objectivity-oriented strategies (n = 4); plus, one "mixed" category (n = 11). Strategies were rarely theoretically derived. Conclusions: Current research of tested strategies for verbally providing medical information is marked by great heterogeneity in methods and outcomes, and lack of theory-driven approaches. The list of strategies could be used to analyse real life communication. Practice implications: Findings may aid the harmonization of future efforts to develop empirically-based information provision strategies to be used in clinical and teaching settings.